Thermal performance in circular tube with Co/counter-twisted tapes - Chokphoemphun, Suriya; Hinthao, Chayodom; Eiamsa-Ard, Smith; Promvonge, Pongjet; Thianpong, Chinaruk (My University, 2014)
Thiswork presents an experimental study on enhanced heat transfer and pressure loss characteristics in a tube having a uniform heat-fluxed wall by using small double and triple co- and counter-twisted tapes at two twist ratios, y/w=4 and 4.5. The investigation has been conducted for Reynolds number from 5300-20,000. The experimental results of the heat transfer and pressure drop are proposed in terms of Nusselt number and friction factor, respectively.The experimental results reveal thatthe maximum TEF for the triple counter-twisted tapesat smaller twist ratio isabout 1.26. © (2014) Trans Tech Publications, Switzerland.
Keywords: Co-twisted tape; Counter-twisted tape; Friction factor; Nusselt number; Thermal performance